متطلبات إقامة برنامج الصيانة المنتجة الشاملة : دراسة ميدانية في مصنع الغزل و النسيج في الموصل - السمان، ثائر أحمد سعدون; الصواف، محفوظ حمدون (جامعة الموصل - كلية الإدارة والاقتصاد, 2005)
The research aims at defining the essence of the total production maintenance and its requirements, where the increases competition has led the productive organization to search for any character that will increase the chances of success. Then it begins to depend on the modern programs which requires adopting a new planning to deal with the maintenance and its control instruments to achieve the objectives. So, achieving the characteristics and delivery at the exact time, decreasing the storage level, reaching the zero defects and the high flexibility to meet the needs of consumers, require depending on untraditional methods in managing and executing maintenance through heading towards the system of the global productive maintenance. So, this paper is an attempt to apply the program of total production maintenance in Mosul factory through recognizing the adopted maintenance style presenting proposals for developing this system in the factory which will enable the factory management to adopt the system in the future in order to improve work sufficiency of production facilities. This research reached set of conclusions and recommendations.
Keywords: الموصل -- إدارة الجودة الشاملة -- المنشآت الصناعية -- صناعة الغزل و النسيج -- خطوط الانتاج -- العراق